Floristic Composition of Weeds in Paddy Fields in Mahendranagar, Nepal - Bhatt, M. D.; Tewari, A.; Singh, S. P. (Ecoprint: An International Journal of Ecology, 2010)
Field experiments were conducted during 2004 and 2005 in paddy fields to evaluate the floristic composition of weeds, in lowland and upland areas of Mahendranagar, Nepal. A total of 61 weed species belonging to 42 genera and 23 families were recorded. Of the 23 families, Cyperaceae was the largest (13 spp.), followed by Poaceae (11 spp.), Euphorbiaceae (4 spp.), Amaranthaceae, Commelinaceae and Asteraceae (3 spp. each), Polygonaceae (2 spp.) and one species each belonged to Apiaceae, Acanthaceae, Alismataceae, Pontederiaceae, Leguminosae, Convolvulaceae, Eriocaulaceae, Marsileaceae, Malvaceae, Oxalidaceae, Onagraceae, Parkeriaceae, Portulaceae, Rubiaceae and Verbenaceae. The number of weed species was higher in upland (55) when compared with the lowland sites (48). On the basis of Importance Value Index (IVI) dominating weed species in paddy fields were: Fimbristylis miliacea (13.4), Lindernia oppositifolia (13.2), Eleocharis atropurpurea (13.1), Ageratum conyzoides (13.0), Cyperus iria (13.0), Echinochloa crus-galli (11.9), Ischaemum rugosum (11.7), Echinochloa colona (11.4), Cyperus difformis (11.1) and Schoenoplectus juncoides (11.0). Besides dicots and monocots, two species of pteridophytes (Ceratopteris thalictriodes and Marsilea minuta) were also recorded in lowland paddy fields. Key words: Paddy, weeds, upland, lowland, IVI. DOI: 10.3126/eco.v16i0.3468 ECOPRINT 16: 15-19, 2009